Komparasi Laju Deforestasi Kabupaten Berbasis Agraris dengan Kabupaten Berbasis Industri Pertambangan di Pulau Sumbawa Periode 2017–2024 - Sulaiman; Taslim Sjah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The dry tropical forests of Sumbawa Island represent critical hydrological buffers that are highly vulnerable to disturbance yet face mounting land-conversion pressure from land-based economic expansion. Sumbawa Island exhibits a contrasting dual economic structure: agrarian districts dependent on maize cultivation and an industrial district dominated by copper-gold mining. This study comparatively analyzes deforestation rates between these two groups during the 2017–2024 period to identify which economic sector exerts the greatest pressure on forest cover. A quantitative comparative method based on spatial data analysis was employed, utilizing the ESRI Land Cover 10m dataset derived from Sentinel-2 imagery for 2017 and 2024, processed using the Tabulate Area function in ArcGIS Pro under the UTM Zone 50S, WGS 84 projection system. Deforestation rates were calculated using both an absolute approach in hectares per year and a relative approach through Puyravaud's (2003) Compound Annual Rate (CAR) formula. Results indicate that all districts experienced declining tree cover throughout the study period. Dompu Regency recorded the highest deforestation rate at −3.44% per year, equivalent to 4,075 hectares per year, followed by Bima Regency at −1.21% per year, Sumbawa Regency at −0.47% per year, and West Sumbawa Regency at −0.41% per year. The mining-based district, West Sumbawa Regency, recorded the lowest deforestation rate despite possessing the largest Gross Regional Domestic Product (GRDP). This finding confirms that economic scale does not directly correlate with deforestation intensity; rather, sectoral governance is the primary determining factor. Regulatory instruments such as reclamation obligations and Forest Area Borrowing-Use Permits have proven effective in constraining the spatial expansion of mining activities, whereas sporadic and atomistic agrarian pressure from maize farming has driven massive forest conversion along forest frontiers.